(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the problem-solving ability of grade IV students in working on story problems based on Newman Error Analysis. The research method used is descriptive with a qualitative approach. The subjects in this study were 21 students in grade IV of SDN 1 Rahayu with high, medium, and low criteria. The data collection technique was carried out by a written test and interviews using a five-question research instrument on problem-solving skills and interview guidelines. The data analysis technique in this study is triangulation. The results of the study showed that the solving ability of grade IV students in solving story problems reached an average of 60%. The factors that cause students to make mistakes are because students are less fluent in reading, lack of understanding of the material, lack of precision, and students are not used to writing answers in a structured and detailed manner.